Implementasi Konseling Individu Berbasis Social Emotional Learning Dalam Mengurangi Perilaku Membolos - Nurwahyuni, Nurwahyuni; Rinaldi, Atfal Wahyu; Pantow, Deswita; Klaudia, Hesti; Hijra, Hijra; Nirmawati, Nirmawati; Nurmin, Nurmin (Universitas Batanghari Jambi, 2025)
This study aims to analyze the implementation of individual counseling based on Social EmotionalLearning(SEL)inreducingtruancyamonghighschoolstudents.Thestudyemploys aqualitativeapproachwithacasestudymethod,involvingstudentswithahistoryoftruancy,as well as school counselors and homeroom teachers as key informants. Data were collected through in-depth interviews, participatory observations, and school document analysis. Data analysis was conducted using thematic analysis to identify patterns and key findings related to changes in students’ behavior after participating in SEL-based individual counseling. The results indicate that the majority of students who participated in counseling showed an improvement in attendance and academic engagement. The SEL components that contributed the most to behavioral changes were self-awareness, self-management, and social relationship skills. The supporting factors for the implementation of this program included school support and parental involvement, whereas the inhibiting factors were initial resistance from students andlimitedcounselingtime.Comparedtopreviousstudies,theSEL-basedindividualcounseling approach proved to be more effective in addressing absenteeism on a personalized level than classroom-based SEL interventions.